EFEK PENAMBAHAN LEVEL VITAMIN E DAN SELENIUM DALAM PAKAN TERHADAP PERFORMA AYAM PETELUR YANG DIINSEMINASI BUATAN - Lidyawati, Anna; Khopsoh, Binti; Haryuni, Nining (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2018)
The purpose of this research was to determine the effect of adding vitamin E and selenium as feed additives on the performance of artificially inseminated laying hens. The material used in this research was a 34-week-old laying hen strain of Isa Brown as many as 100 laying hens in artificial insemination. Artificial insemination was done by crossing buras chickens with females from laying hens. Artificial insemination was done every 4 days. This research used statistical analysis using ANOVA with Completely Randomized Design (CRD) which used 5 treatments and 5 replications where each treatment and each replication consisted of 4 laying hens. If there is a real difference or very real influence,it will continued using Duncan's test. The treatment feed in this research are as follows: P0 = Basal Feed, P1 = Basal Feed + 21.75 ppm vitamin E and 0.23 ppm selenium, P2 = Basal Feed + 43.5 ppm vitamin E and 0.46 ppm selenium, P3 = Basal Feed + 65.25 ppm vitamin E and 0.69 ppm selenium, P4 = Basal Feed + 87 ppm vitamin E and 0.92 ppm selenium. The results obtained in this research were the addition of vitamin E and selenium in feed had a significant effect (P <0.05) on feed consumption and protein consumption, and also had a very significant effect (P <0.01) on Hen Day Production (HDP) and FCR, but it did not provide significant effect (P> 0.05) on egg weight. The best dose addition of vitamin E and selenium is vitamin E by 87 ppm and Selenium by 0.92 ppm. Keywords : Artificial Insemination, Feed Additives, Performance Of Laying Hens, Selenium, Vitamin E